Acute sacral epidural abscess following local anaesthetic injection. Issue 692 (June 1983) - Rustin, M. H.; Flynn, M. D.; Coomes, E. N.
Abstract : Spinal epidural abscesses are uncommon infections of the central nervous system. Delay in making the diagnosis increases the morbidity and mortality because irreversible neurological damage occurs during this time. We report a 45-year-old male who developed an acute sacral epidural abscess following a local anaesthetic injection given for the relief of low back pain. We believe this is the first documented case of a local anaesthetic injection causing an acute sacral epidural abscess.